O E C D Economic Surveys: India 2014 - O E C D Publication (New Delhi O E C D Publication, 2014)
OECD's 2014 Economic Survey of India examines recent economic developments, policies and prospects. Special chapters cover health, the manufacturing sector and economic participation of women.
Keywords: ECONOMIC POLICY - INDIA; ECONOMIC CONDITIONS - INDIA